Basic Sanitation Factors Affecting Diarrheal Disease in Toddlers: Observations in the Working Area of Tambakrejo Health Center - Debora Lasma Uli Sigalingging; Setiawan; Suprijandani; Ngadino; Ahmad Daudsyah Imami (Jurnal teknologi Kesehatan Borneo, 2024)
Diarrhoea is a condition in which a person feels defecation with liquid or watery stools, generally occurring more than three times per day. Diarrhoea in toddlers in the area work Puskesmas Tambakrejo City Surabaya for the last 3 years (2020-2023) has increased. The increase shows an increasing trend of cases so it is necessary to know the cause. The purpose of this study was to identify factors - factors causes of diarrhoea in toddlers, namely: clean water facilities, healthy toilet facilities, sewerage and garbage disposal facilities in the homes of toddlers with diarrhoea. This study uses descriptive research with a approach cross-sectional using 47 samples. This research is a survey study by making observations at the same time or once upon a time with the help of questionnaires and interviews with mothers of toddlers. The results showed that as many as 80.9% of respondents who had clean water facilities met requirements, 80.9% of respondents' healthy latrine facilities met the requirements, 95.7% of respondents' sewerage met the requirements and 61.7% of waste disposal facilities met the requirements. The conclusion of this study shows that all variables studied fulfil the requirements of the applicable health standards. fulfil the requirements by the applicable standard quality of health. The region's community is expected to implement clean and healthy living behaviour.